Development of Articulate Storyline 3-Based Interactive Media to Enhance Conceptual Understanding of the Immune System among Madrasah Aliyah Students - Nurlita, Desi; Adlini, Miza Nina (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to develop and evaluate the validity, practicality, and effectiveness of interactive learning media based on Articulate Storyline 3 for teaching the Immune System topic to eleventh-grade students at Madrasah Aliyah. The developed media integrates learning materials, animations, videos, interactive quizzes, and learning navigation features. This study employed a Research and Development (R&D) approach using the 4D development model (Define, Design, Development, and Disseminate). The product was tested on 27 eleventh-grade students at MAN 1 Medan. The research instruments included material expert and media expert validation sheets, teacher and student response questionnaires, and conceptual understanding tests. The collected data were analyzed using descriptive quantitative analysis through validity, practicality, and N-Gain assessments. The results indicated that the developed media achieved a very high level of validity, with validation scores of 97% from material experts and 99% from media experts. The practicality assessment based on teacher and student responses showed scores of 96% and 96%, respectively, indicating that the media was categorized as highly practical. Students’ average conceptual understanding scores increased from 48.22 in the pretest to 85.70 in the posttest, with an N-Gain score of 0.71, categorized as high. These findings suggest that interactive learning media based on Articulate Storyline 3 has the potential to support students’ conceptual understanding of the Immune System topic. However, this study was limited to a single-class trial involving 27 students.